THE RESPONSIBILITIES OF THE INDONESIAN WAQF BOARD (BWI) IN HANDLING INDONESIAN WAQF CASH - Septiana, Diva Agi; Rinda Asytuti; Nasywa Awalyah; Naila Septiani (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2025)
This study examines the strategic role of the Indonesian Waqf Board (BWI) in managing and growing productive waqf (Islamic waqf) in Indonesia. It focuses on enhancing governance, developing waqf instruments, and its contribution to community economic empowerment. A textbook research method was used to conduct this research. Twenty international journal articles and several relevant SINTA-accredited national sources were examined. The results show that Indonesian waqf has tremendous potential, particularly in the cash waqf sector, which reached IDR 1.4 trillion in March 2022. However, due to low public education, weak nazhir capacity, and the lack of a technology-based management system, this potential has not been fully utilized. Through guiding, certifying, and supervising nazhir and encouraging productive waqf management through innovative instruments such as Cash Waqf Linked Sukuk (CWLS), BWI plays a vital role in strengthening the national waqf ecosystem. This innovation not only maintains the value of waqf funds but also has social and economic effects for the community by financing education, health, and microeconomic empowerment. This research confirms that synergy between th Therefore, waqf can function as a sharia economic instrument that not only serves as a form of worship but also contributes to the development and social welfare of the nation.